High-strength high-toughness composite silicon carbide ceramic and preparation method thereof

Through the combination of hot press sintering and composite reinforced phase, the problem of insufficient toughness of silicon carbide ceramic materials in the field of dry air sealing is solved, and high-strength and high-toughness composite silicon carbide ceramic materials are prepared, which improves its mechanical properties and application range.

CN119409508APending Publication Date: 2025-02-11ZHEJIANG DONGXIN NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411345196.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing silicon carbide ceramic materials have high strength but insufficient toughness in the field of dry air sealing, which limits their service life and application range.

Method used

The hot press sintering method combined with the composite reinforced phase is used. By adding alumina and yttrium oxide to the silicon carbide ceramic as sintering aid, nanotitanium nitride and microsilicon carbide whiskers as reinforced phases, high strength and high toughness of silicon carbide Preparation of ceramic materials.

Benefits of technology

A high-strength, high-toughness composite silicon carbide ceramic material with high volume density, bending strength exceeding 495MPa and fracture toughness exceeding 4.7MPa·m1/2 was successfully prepared, which significantly improved its mechanical properties and toughness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409508A_ABST
    Figure CN119409508A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of high-strength and high-toughness composite silicon carbide ceramic, which comprises the following steps: mixing 70-82 parts of micron-sized alpha-silicon carbide powder, 5-15 parts of a mixed reinforced phase, 5-10 parts of a sintering aid, 1.9-2.1 parts of a dispersant and 0.9-1.1 parts of a binder to obtain a powder raw material, adding deionized water into the powder raw material, and carrying out ball milling to obtain water-based slurry; carrying out spray granulation on the water-based slurry to prepare spherical granulation powder; and adding the spherical granulation powder into a graphite mold, putting the graphite mold into a hot-pressing sintering furnace, heating to a sintering temperature, and carrying out hot-pressing sintering to obtain the high-strength and high-toughness composite silicon carbide ceramic. By adopting the method disclosed by the invention, the high-performance silicon carbide ceramic material with higher mechanical property and higher toughness can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-strength and high-toughness composite silicon carbide ceramic and a preparation method thereof, in particular to a hot pressing and sintering preparation method of a yttrium aluminum garnet system silicon carbide ceramic material. Background Art

[0002] As a new type of shaft end sealing technology that uses gas for sealing under non-contact conditions, dry gas seals are widely used in various production fields. Since the dynamic ring in the dry gas seal assembly needs to work for a long time in a high-pressure working environment, the material needs to have high strength, high toughness and other properties. At present, silicon carbide ceramics are the most commonly used dry gas seal dynamic ring material. Its high mechanical properties and thermodynamic properties can well match the performance requirements of dry gas seal assemblies. Although silicon carbide ceramic materials have high strength and stable chemical properties, as a typical ceramic material, they also have problems such as poor toughness and fragility, which limits their service life in the field of dry gas sealing. Therefore, this industry chooses to improve the mechanical properties of silicon carbide ceramic sealing materials by improving sintering methods and composite doping, explore the future direction of silicon carbide ceramic performance development, and broaden its application range. In actual production, silicon carbide ceramic materials are mainly prepared by reaction sintering and pressureless sintering. The silicon carbide ceramics obtained by reaction sintering have higher purity but their mechanical properties are significantly lower than those obtained by pressureless sintering, so the latter has more applications.

[0003] With the continuous development of sintering technology, hot pressing sintering has entered people's field of vision as a more advanced preparation method for high-performance ceramics. Hot pressing sintering is developed on the basis of pressureless sintering. It is based on the heating and sintering of the green body composed of silicon carbide powder, and a certain external pressure is applied to the green body along the axial direction through mechanical action. The external pressure provides additional driving force for the entire sintering process, so that the green body can quickly complete densification and realize the simultaneous sintering and forming processes. Compared with pressureless sintering, hot pressing sintering can significantly improve the overall mechanical properties of silicon carbide ceramics. At the same time, the temperature, time and amount of sintering aids required for the densification of silicon carbide materials can be significantly reduced.

[0004] In addition to the improvement of sintering technology, strengthening and toughening ceramics through composite reinforcement phases has become an effective way to enhance the performance of silicon carbide ceramics. In recent years, a variety of reinforcement and toughening composite systems have shown remarkable results. Among all the reinforcement and toughening methods, by combining different types of ceramic phases together, using a reasonably composed second phase (nanoparticles, fibers, whiskers, etc.), and directional improvement of the physical and chemical properties of ceramic materials, a multiphase composite method with improved comprehensive performance has been proven to be a very effective method. By combining with advanced sintering methods such as hot pressing sintering, high-performance silicon carbide ceramic materials can be obtained.

[0005] At present, there are relevant patent reports on the preparation of high-performance silicon carbide ceramic materials by hot pressing sintering and composite reinforcement. For example, the patent with publication number CN109592983A discloses a method for preparing silicon carbide ceramics by hot pressing sintering. The method uses silicon carbide powder as raw material and a certain proportion of cerium oxide, yttrium oxide, and erbium oxide as sintering aids to prepare high thermal conductivity silicon carbide ceramics with a thermal conductivity of 150W / (m·K), but the relevant mechanical performance indicators are not reported. The patent with publication number CN117700231A discloses a method for preparing high-strength silicon carbide ceramics by hot pressing sintering and a preparation method thereof. It mainly uses submicron silicon carbide powder as raw material and YAG composed of aluminum oxide and yttrium oxide as sintering aid. High-strength silicon carbide ceramic materials are prepared by hot pressing sintering, and the maximum bending strength is 713MPa. The Chinese patent with publication number CN111138200A reported a high-performance multi-phase composite reinforced silicon carbide ceramic material, which mainly used α-silicon carbide as raw material, yttrium aluminum garnet as sintering aid, and composited graphene, zirconium diboride, and silicon carbide whiskers as reinforcement phases. The silicon carbide ceramic obtained by liquid phase sintering has a flexural strength of 400-420MPa and a good dry friction coefficient. The above patents have achieved valuable results in the hot pressing sintering and composite reinforcement of silicon carbide ceramics, but lack an organic combination of the two reinforcement methods; the industry is in urgent need of obtaining silicon carbide ceramic materials with both excellent strength and toughness.

[0006] In conventional yttrium aluminum garnet, the weight ratio of aluminum oxide to yttrium oxide is 4.3:5.7. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide a method for preparing silicon carbide ceramics having both high strength and high toughness.

[0008] In order to solve the above technical problems, the present invention provides a method for preparing high-strength and high-toughness composite silicon carbide ceramics, comprising the following steps:

[0009] 1) Slurry preparation:

[0010] 70 to 82 parts of micron-grade α-silicon carbide powder, 5 to 15 parts of mixed reinforcing phase, 5 to 10 parts of sintering aid, 1.9 to 2.1 parts of dispersant, and 0.9 to 1.1 parts of binder are mixed as powder raw materials; the above parts are parts by weight;

[0011] Add deionized water to the powder raw material and perform ball milling (in a ball mill) to obtain a water-based slurry; the weight ratio of the powder raw material to deionized water is 1:1.4-1.6;

[0012] 2) Spray granulation:

[0013] The water-based slurry obtained in step 1) is subjected to spray granulation to prepare spherical granulated powder;

[0014] 3) Hot pressing sintering:

[0015] The spherical granulated powder obtained in step 2) is added into a graphite mold (the graphite mold can be filled up), and is placed in a hot pressing sintering furnace and heated to a sintering temperature for hot pressing sintering to obtain a high-strength and high-toughness composite silicon carbide ceramic.

[0016] Note: After hot pressing and sintering, the pressure is released and the furnace is cooled.

[0017] As an improvement to the preparation method of the high-strength and high-toughness composite silicon carbide ceramic of the present invention, in the step 1):

[0018] The mixed reinforcement phase is composed of nano titanium nitride particles and micron silicon carbide whiskers, and the weight ratio of the nano titanium nitride particles to micron silicon carbide whiskers is 1:(1±0.05);

[0019] The sintering aid is composed of aluminum oxide and yttrium oxide, and the aluminum oxide accounts for 43% to 50% of the weight of the sintering aid (aluminum oxide: yttrium oxide = 4.3:5.7 to 1:1);

[0020] Polyethylene glycol is a dispersant and polyvinyl alcohol is a binder.

[0021] As a further improvement of the preparation method of the high-strength and high-toughness composite silicon carbide ceramic of the present invention, in step 2):

[0022] The slurry feed rate in the spray granulation stage is 40-60 mL / min, the hot air inlet temperature is 250-300°C, the outlet temperature is 70-90°C, and the centrifugal atomizer adjustment frequency is 40-70 Hz.

[0023] As a further improvement of the preparation method of the high-strength and high-toughness composite silicon carbide ceramic of the present invention: the spherical granulated powder obtained in step 2) is added to a graphite mold, first pre-pressed at a pressure of 35 to 45 MPa for 4 to 6 minutes, then placed in a hot pressing sintering furnace and heated to the sintering temperature for hot pressing sintering to obtain a high-strength and high-toughness composite silicon carbide ceramic.

[0024] As a further improvement of the preparation method of the high-strength and high-toughness composite silicon carbide ceramic of the present invention, the hot pressing sintering in step 3) is:

[0025] The temperature is raised to the set sintering temperature at a heating rate of 5 to 20°C / min for heat preservation and sintering. During the heating process, the external pressure is evenly increased from the initial pressure to the set sintering pressure;

[0026] Then, the sintering is carried out at a set sintering temperature and a set sintering pressure for 50 to 70 minutes;

[0027] The initial pressure (external pressure during the heating stage) is 5-10 MPa, and the set sintering pressure (external pressure during the heat preservation sintering stage) is 20-40 MPa;

[0028] The set sintering temperature is 1820~1980℃.

[0029] Description: During the heating and insulation stages, external pressure is applied through mechanical action; after the insulation sintering is completed, the mold is demolded and the silicon carbide ceramic material of the required size is obtained through subsequent conventional grinding processing.

[0030] As a further improvement of the preparation method of the high-strength and high-toughness composite silicon carbide ceramic of the present invention:

[0031] In the step 2), preferably, the slurry feed rate is 40 mL / min, the hot air inlet temperature is 280° C., the outlet temperature is 86° C., and the centrifugal atomizer frequency modulation is 48 Hz;

[0032] In the step 3), preferably, the heating rate is 10°C / min, the sintering temperature is 1980°C, the initial pressure is 5Mpa, the sintering pressure is 30Mpa, and the heat preservation sintering time is 60min.

[0033] As a further improvement to the preparation method of the high-strength and high-toughness composite silicon carbide ceramic of the present invention: 77 parts of micron α-silicon carbide powder, 5 parts of nano titanium nitride particles, 5 parts of micron silicon carbide whiskers, 5 parts of aluminum oxide, 5 parts of yttrium oxide, 2 parts of polyethylene glycol and 1 part of polyvinyl alcohol are mixed as powder raw materials.

[0034] The present invention also provides high-strength and high-toughness composite silicon carbide ceramics prepared by any of the above methods.

[0035] The high-strength and high-toughness composite silicon carbide ceramic obtained by the method of the present invention has a volume density of more than 3.1 g / m when tested in a strip sample of 3*4*40 mm. 3 , flexural strength>495MPa, fracture toughness>4.7MPa·m 1 / 2 .

[0036] The invention discloses a method for preparing silicon carbide ceramics by hot pressing and sintering, using aluminum oxide and yttrium oxide as sintering aids, nano titanium nitride and silicon carbide whiskers as reinforcing phases.

[0037] The technical advantage of the present invention is that a high-strength and high-toughness silicon carbide ceramic material is successfully prepared by using a hot pressing sintering method, a composite reinforcement mechanism and a yttrium aluminum garnet sintering aid system. The present invention uses aluminum oxide and yttrium oxide as sintering aids. The liquid phase yttrium aluminum garnet generated by their reaction at high temperature transforms the mass transfer mode of the ceramic powder from simple diffusion to viscous flow, effectively promoting the sintering of silicon carbide ceramics; the reinforcement phase composed of nano-titanium nitride and micron silicon carbide whiskers increases the strength and toughness of the ceramic through crack transfer, pull-out effect, crack pinning and other mechanisms; the hot pressing sintering process applies external pressure through mechanical action, which provides an additional sintering driving force for the entire sintering process, reduces the sintering difficulty of silicon carbide ceramics, and can obtain high-performance silicon carbide ceramic materials with higher mechanical properties and stronger toughness, which has high practical value in the field of special ceramics such as dry gas seals. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The specific implementation modes of the present invention are further described in detail below with reference to the accompanying drawings.

[0039] Figure 1 From left to right are cross-sectional scanning electron microscope images of Example 1-3, Example 2-3, and Example 3-3. DETAILED DESCRIPTION

[0040] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto:

[0041] The particle size of micron α-silicon carbide powder is 5 to 10 microns;

[0042] The particle size of the nano titanium nitride particles is 20 to 30 nanometers;

[0043] The crystal phase of micron silicon carbide whiskers is β-silicon carbide, with a diameter of 2 to 3 microns and a length of 40 to 80 microns;

[0044] The remaining components in the raw materials (such as alumina, yttrium oxide, etc.) are required to be able to pass through a 300-mesh sieve.

[0045] Parts are by weight.

[0046] The stirring speed is 400-500 rpm.

[0047] Example 1-1: A method for preparing high-strength and high-toughness silicon carbide ceramics, comprising the following steps in sequence:

[0048] 1) Powder raw material composition: 82 parts of micron α-silicon carbide powder, 2.5 parts of nano titanium nitride particles, 2.5 parts of micron silicon carbide whiskers, 5 parts of aluminum oxide, 5 parts of yttrium oxide, 2 parts of polyethylene glycol, and 1 part of polyvinyl alcohol;

[0049] 2) adding the weighed powder raw material into a ball mill barrel, adding deionized water 1.5 times the weight of the powder raw material, stirring, and ball milling for about 180 minutes to prepare a water-based slurry;

[0050] 3) preparing spherical granulated powder by spray granulation of the water-based slurry;

[0051] The parameters of the spray granulation tower are: hot air inlet temperature 280°C, outlet temperature 86°C, centrifugal atomizer modulation frequency 48Hz, after the granulation tower temperature reaches the facility parameters, the feed pump is turned on, and the water-based slurry is introduced into the granulation tower at a flow rate of 40mL / min, and finally the ceramic granulation powder with uniform particle size and size (particle size is about 20-50μm) is obtained;

[0052] 4) Add the ceramic granulation powder into the graphite mold of the hot pressing sintering furnace and apply pressure by mechanical action. First, pre-press at a pressure of 40 MPa for 5 minutes, then start the heating process, and heat up to the insulation temperature of 1820°C at a heating rate of 10°C / min. As the heating process proceeds, the pressure is increased from 5MPa to 30MPa, and then sintered at 1820°C and 30Mpa for 60 minutes; after the insulation is completed, the pressure is released and the furnace is cooled.

[0053] That is, the initial external pressure applied was 5 MPa, and the external pressure during the heat preservation stage was 30 MPa.

[0054] 5) The sintered silicon carbide ceramic is demolded to obtain a high-strength and high-toughness silicon carbide ceramic, which is named 1-1.

[0055] Then, according to actual needs, silicon carbide ceramic materials of various sizes can be obtained through precision processing.

[0056] The strip samples were made into 3*4*40 mm strip samples and tested according to conventional methods (for example, referring to GB / T 25995-2010, GB / T6569-2006, GB / T 10700-2006). The bulk density, flexural strength and fracture toughness of the samples are shown in Table 1 below.

[0057] The silicon carbide ceramic obtained in Example 1-1 has good sintering density and mechanical properties.

[0058] Example 1-2: Compared with Example 1-1, the insulation temperature in step 4) is changed from 1820°C to 1900°C; the rest is the same as Example 1-1.

[0059] The final sample was named 1-2. The bulk density, flexural strength and fracture toughness of the sample are shown in Table 1 below.

[0060] As the sintering temperature increases, the sintering density of sample 1-2 increases and the mechanical properties are also higher.

[0061] Example 1-3: Compared with Example 1-1, the insulation temperature in step 4) is changed from 1820°C to 1980°C; the rest is the same as Example 1-1.

[0062] The samples finally obtained were named 1 to 3. The bulk density, flexural strength and fracture toughness of the samples are shown in Table 1 below.

[0063] As the sintering temperature further increases, the performance of samples 1-3 is further improved, indicating that 1980℃ is the optimal sintering insulation temperature.

[0064] Example 2-1: Relative to Example 1-1, the powder raw material in step 1) is changed to consist of the following components: 77 parts of micron α-silicon carbide powder, 5 parts of nano titanium nitride particles, 5 parts of micron silicon carbide whiskers, 5 parts of aluminum oxide, 5 parts of yttrium oxide, 2 parts of polyethylene glycol, and 1 part of polyvinyl alcohol.

[0065] The rest is the same as Example 1-1.

[0066] The final sample was named 2-1. The bulk density, flexural strength and fracture toughness of the sample are shown in Table 1 below.

[0067] The mechanical properties of sample 2-1 have been improved to a certain extent due to the increase in the proportion of the reinforcing phase.

[0068] Example 2-2: Compared with Example 2-1, the insulation temperature in step 4) is changed from 1820°C to 1900°C; the rest is the same as Example 2-1.

[0069] The final sample was named 2-2. The bulk density, flexural strength and fracture toughness of the sample are shown in Table 1 below.

[0070] As the sintering temperature increases, the performance of sample 2-2 is further improved compared to sample 2-1, which once again verifies the importance of increasing the sintering insulation temperature for densification sintering.

[0071] Example 2-3: Compared with Example 2-1, the insulation temperature in step 4) is changed from 1820°C to 1980°C; the rest is the same as Example 2-1.

[0072] The final sample was named 2-3. The bulk density, flexural strength and fracture toughness of the sample are shown in Table 1 below.

[0073] Sample 2-3 has good sintering density, high density, and the most excellent mechanical properties, and is a preferred embodiment of the present invention.

[0074] Example 3-1: Relative to Example 1-1, the powder raw material in step 1) is changed to consist of the following components: 72 parts of micron α-silicon carbide powder, 7.5 parts of nano titanium nitride particles, 7.5 parts of micron silicon carbide whiskers, 5 parts of aluminum oxide, 5 parts of yttrium oxide, 2 parts of polyethylene glycol, and 1 part of polyvinyl alcohol.

[0075] The rest is the same as Example 1-1.

[0076] The final sample was named 3-1. The bulk density, flexural strength and fracture toughness of the sample are shown in Table 1 below.

[0077] Compared with sample 2-1, after further increasing the proportion of the reinforcing phase, the density and mechanical properties of the sample decreased, indicating that excessively increasing the proportion of the reinforcing phase will lead to a decrease in sample performance.

[0078] Example 3-2: Compared with Example 3-1, the insulation temperature in step 4) is changed from 1820°C to 1900°C; the rest is the same as Example 3-1.

[0079] The final sample was named 3-2. The bulk density, flexural strength and fracture toughness of the sample are shown in Table 1 below.

[0080] Example 3-3: Compared with Example 3-1, the insulation temperature in step 4) is changed from 1820°C to 1980°C; the rest is the same as Example 3-1.

[0081] The final sample was named 3-3. The bulk density, flexural strength and fracture toughness of the sample are shown in Table 1 below.

[0082] Example 4: Compared with Example 2-3, the "5 parts of aluminum oxide, 5 parts of yttrium oxide" in the powder raw material is changed to "4.3 parts of aluminum oxide, 5.7 parts of yttrium oxide"; the rest is the same as Example 2-3.

[0083] The final sample was named 4. The bulk density, flexural strength and fracture toughness of the sample are shown in Table 1 below.

[0084] The performance of sample 4 has declined to a certain extent compared with samples 2-3, which shows that if the sintering aid is completely in accordance with the conventional proportion of yttrium aluminum garnet, it will lead to a decline in sample performance.

[0085] Table 1 Mechanical properties of silicon carbide ceramic samples in various embodiments and comparative examples

[0086]

[0087]

[0088] Note: The sample size for the above test is 3*4*40mm strip sample.

[0089] Comparative Example 1: Compared with Example 2-3, the insulation temperature is reduced from 1980°C to 1720°C; the rest is the same as Example 2-3.

[0090] The sample finally obtained is named Comparative Example 1. The bulk density, flexural strength and fracture toughness of the sample are as described in Table 1 above.

[0091] Comparative Example 2: Compared with Example 2-3, "5 parts of nano-titanium nitride particles and 5 parts of micron silicon carbide whiskers" are changed to "10 parts of nano-titanium nitride particles"; the rest is the same as Example 2-3.

[0092] The sample finally obtained is named Comparative Example 2. The bulk density, flexural strength and fracture toughness of the sample are as described in Table 1 above.

[0093] Comparative Example 3: Compared with Example 2-3, "5 parts of nano titanium nitride particles, 5 parts of micron silicon carbide whiskers" is changed to "10 parts of micron silicon carbide whiskers"; the rest is the same as Example 2-3.

[0094] The sample finally obtained is named Comparative Example 3. The bulk density, flexural strength and fracture toughness of the sample are as described in Table 1 above.

[0095] Comparative Example 4: relative to Example 2-3, "5 parts of nano-titanium nitride particles" are changed to "5 parts of nano-silicon carbide particles"; the rest is the same as Example 2-3.

[0096] The sample finally obtained is named Comparative Example 4. The bulk density, flexural strength and fracture toughness of the sample are as described in Table 1 above.

[0097] Comparative Example 5: Compared with Example 2-3, "5 parts of nano-titanium nitride particles" is changed to "5 parts of nano-titanium carbide particles"; the rest is the same as Example 2-3.

[0098] The sample finally obtained is named Comparative Example 5. The bulk density, flexural strength and fracture toughness of the sample are as described in Table 1 above.

[0099] Comparative Example 6: Compared with Example 2-3, the pressure in the heat preservation stage of hot pressing sintering is changed to 60 MPa; the rest is the same as Example 2-3.

[0100] The sample finally obtained is named Comparative Example 6. The bulk density, flexural strength and fracture toughness of the sample are as described in Table 1 above.

[0101] Comparative Example 7: Compared with Example 2-3, the holding time of hot pressing sintering is changed to 120 min; the rest is the same as Example 2-3.

[0102] The sample finally obtained is named Comparative Example 7. The bulk density, flexural strength and fracture toughness of the sample are as described in Table 1 above.

[0103] Finally, it should be noted that the above examples are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.

Claims

1. A method for preparing high-strength and high-toughness composite silicon carbide ceramics, characterized in that The following steps are involved: 1) Slurry preparation: 70 to 82 parts of micron-grade α-silicon carbide powder, 5 to 15 parts of mixed reinforcing phase, 5 to 10 parts of sintering aid, 1.9 to 2.1 parts of dispersant, and 0.9 to 1.1 parts of binder are mixed as powder raw materials; the above parts are parts by weight; Deionized water is added to the powder raw material for ball milling to obtain a water-based slurry; the weight ratio of the powder raw material to deionized water is 1:1.4-1.6; 2) Spray granulation: The water-based slurry obtained in step 1) is subjected to spray granulation to prepare spherical granulated powder; 3) Hot pressing sintering: The spherical granulated powder obtained in step 2) is added into a graphite mold, and placed into a hot pressing sintering furnace and heated to the sintering temperature for hot pressing sintering to obtain a high-strength and high-toughness composite silicon carbide ceramic.

2. The method for preparing a high-strength and high-toughness composite silicon carbide ceramic according to claim 1, characterized in that In the step 1): The mixed reinforcement phase is composed of nano titanium nitride particles and micron silicon carbide whiskers, and the weight ratio of the nano titanium nitride particles to micron silicon carbide whiskers is 1:(1±0.05); The sintering aid is composed of aluminum oxide and yttrium oxide, and the aluminum oxide accounts for 43% to 50% of the weight of the sintering aid; Polyethylene glycol is a dispersant and polyvinyl alcohol is a binder.

3. The method for preparing a high-strength and high-toughness composite silicon carbide ceramic according to claim 2, characterized in that In the step 2): The slurry feed rate in the spray granulation stage is 40-60 mL / min, the hot air inlet temperature is 250-300°C, the outlet temperature is 70-90°C, and the centrifugal atomizer adjustment frequency is 40-70 Hz.

4. The high-strength and high-toughness composite silicon carbide ceramic and the preparation method thereof according to claim 3, characterized in that: The step 3) is: The spherical granulated powder obtained in step 2) is added into a graphite mold, pre-pressed at a pressure of 35-45 MPa for 4-6 minutes, and then placed in a hot pressing sintering furnace and heated to the sintering temperature for hot pressing sintering to obtain a high-strength and high-toughness composite silicon carbide ceramic.

5. A high-strength and high-toughness composite silicon carbide ceramic and a preparation method thereof according to any one of claims 1 to 4, characterized in that Hot pressing sintering in step 3): The temperature is raised to the set sintering temperature at a heating rate of 5 to 20°C / min for heat preservation and sintering. During the heating process, the external pressure is evenly increased from the initial pressure to the set sintering pressure; Then, the sintering is carried out at a set sintering temperature and a set sintering pressure for 50 to 70 minutes; The starting pressure is 5-10 MPa, and the set sintering pressure is 20-40 MPa; The set sintering temperature is 1820~1980℃.

6. A high-strength and high-toughness composite silicon carbide ceramic and a preparation method thereof according to claim 5, characterized in that: In the step 2), the slurry feed rate is 40 mL / min, the hot air inlet temperature is 280° C., the outlet temperature is 86° C., and the centrifugal atomizer frequency modulation is 48 Hz; In the step 3), the heating rate is 10° C. / min, the sintering temperature is 1980° C., the initial pressure is 5 MPa, and the sintering pressure is 30 MPa.

7. A high-strength and high-toughness composite silicon carbide ceramic and a preparation method thereof according to any one of claims 1 to 6, characterized in that: 77 parts of micron α-silicon carbide powder, 5 parts of nano titanium nitride particles, 5 parts of micron silicon carbide whiskers, 5 parts of aluminum oxide, 5 parts of yttrium oxide, 2 parts of polyethylene glycol and 1 part of polyvinyl alcohol were mixed as powder raw materials.

8. A high-strength and high-toughness composite silicon carbide ceramic prepared by the method of any one of claims 1 to 7.

Citation Information

Patent Citations

  • High-thermal conductivity liquid-phase sintered silicon carbide ceramic and preparation method thereof

    CN109592983A

  • Multiphase composite reinforced low-friction silicon carbide ceramic sealing material and preparation method thereof

    CN111138200A

  • Binary nanometer cooperative reinforcing and toughening silicon carbide ceramics and preparing method thereof

    CN101560105A

  • Method using hot pressed sintering to prepare dry-gas-seal rotating ring

    CN106045521A

  • High-strength silicon carbide ceramic and preparation method thereof

    CN117700231A

Cited By

  • Pressureless sintered silicon carbide refractory ceramic thin-walled tube and preparation method thereof

    CN120841960A

  • High-strength ceramic protection plate for slurry pump and preparation method of high-strength ceramic protection plate

    CN120943647A

  • A high-strength ceramic slag slurry pump guard plate and a preparation method thereof

    CN120943647B

  • High-strength ceramic knife production process

    CN121270278A